(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Proximate biochemical compositions of body muscles of Puntius stigma (male and female) such as moisture, protein, lipid, ash and carbohydrate were determined in freshly caught fishes. Some mineral compositions, such as phosphorous, potassium, magnesium, calcium, zinc, copper, manganese and iron were also evaluated. Some amino acids were also detected during analysis. The moisture content 75.60% was found to be higher in female, while protein 21.50%, fat 2.70%, ash 1.90% and carbohydrate contents of 1.55% were higher in male. In protein analysis of two fishes (male and female), most of the minerals were found in higher in male. But manganese and iron were lower in male. Essential amino acids were also estimated. Nutritional values were higher in males than in females. Overall, the fish has a high nutritional value in terms of protein, fat, vitamin and minerals, which are not common in other foods in Bangladesh. Key words: Puntius stigma, Nutritional value, Freshwater fish species. DOI: 10.3329/bjsir.v44i3.4412 Bangladesh J. Sci. Ind. Res. 44(3),367-370, 2009